Primary Borderline Mucinous Tumors of the Testis: A Case Report and Literature Review. (2nd March 2015) - Funada, Satoshi; Yoshida, Toru; Ito, Masaaki; Kono, Fumihiko; Segawa, Takehiko
Abstract : Ovarian-type epithelial tumors of the testes and paratestes are very rare. Mucinous subtypes of such tumors are extremely rare; only 25 cases have been reported to date. Ovarian-type epithelial tumors are histologically classified into cystadenomas, borderline tumors, and carcinomas. We herein report a case involving a 60-year-old man with a primary borderline mucinous tumor of the testis. He underwent orchiectomy and has developed no recurrence for 4 years. This is the 26th report of a mucinous tumor of the testis in the literature. We also herein review the literature and discuss the etiology, prognosis, and treatment of mucinous tumors of the testes.